1997
DOI: 10.1016/s0006-3495(97)78106-2
|View full text |Cite
|
Sign up to set email alerts
|

The monovalent cation "leak" transport in human erythrocytes: an electroneutral exchange process

Abstract: The mechanism of the "ground permeability" of the human erythrocyte membrane for K+ and Na+ was investigated with respect to a possible involvement of a previously unidentified specific transport pathway, because earlier studies showed that it cannot be explained on the basis of simple electrodiffusion. In particular, we analyzed and described the increase in the (ouabain+bumetanide+EGTA)-insensitive unidirectional K+ and Na+ influxes as well as effluxes (defined as "leak" fluxes) observed in erythrocytes susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…The first evidence for the involvement of two separate pathways in the enhancement of unidirectional Na Although it is now recognised that the first pathway is electrogenic [6,7] whereas the latter is electroneutral [8,9], a common pathway underlying these two transport modes cannot be entirely discounted [14]. However, as has been speculated elsewhere [15,16], it was assumed that the increase of the cation fluxes for RBCs suspended in LIS solutions is mediated by the K It is important to note that, after transferring cells from HIS to LIS solutions, a new steady-state is quickly established, associated with an increase of the internal pH from 7.2 to approximately 7.7 [9] which results in a depolarization from -10 mV to 18.5 mV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evidence for the involvement of two separate pathways in the enhancement of unidirectional Na Although it is now recognised that the first pathway is electrogenic [6,7] whereas the latter is electroneutral [8,9], a common pathway underlying these two transport modes cannot be entirely discounted [14]. However, as has been speculated elsewhere [15,16], it was assumed that the increase of the cation fluxes for RBCs suspended in LIS solutions is mediated by the K It is important to note that, after transferring cells from HIS to LIS solutions, a new steady-state is quickly established, associated with an increase of the internal pH from 7.2 to approximately 7.7 [9] which results in a depolarization from -10 mV to 18.5 mV.…”
Section: Discussionmentioning
confidence: 99%
“…At present, 10 different cation transport pathways and 5 Na + -dependent amino acid transporters have been characterised that can translocate Na + and/or K + across the membrane [4,5] [8,9]. In different studies, both pathways have been identified as the 602 principal pathway responsible for enhanced cation fluxes in LIS media.…”
Section: Introductionmentioning
confidence: 99%
“…The increased K + efflux of irradiated erythrocytes correlates with the increase of the K + concentration of the supernatant during the storage [22]. This K + 'leak' is due to a transport molecule and no passive event as assumed so far [23]. Energy doses in the range of 15 to 30 Gy provide comparable fluxes [21].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigations we were able to demonstrate that the LIS effect can be easily ascribed to a K + (Na + )/H + exchanger. This explanation is based on findings that the residual K + transport does not depend on the transmembrane potential [8,9,10], theoretical calculations [11], and a demonstration of a 1 : 1 exchange of K + and H + under LIS conditions [12]. In addition, the non-selective, voltage-dependent cation (NSVDC) channel has to be taken into consideration [13,14,15].…”
Section: Introductionmentioning
confidence: 99%